Pengaruh Disiplin Kerja dan Motivasi terhadap Peningkatan Kinerja Pegawai UPTD Puskesmas Kayu Laut Panyabungan Selatan - Nur Laili; Sari Fitri; Mufti Fahrizal (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Employee performance in primary healthcare services is closely related to internal factors such as work discipline and motivation. In the context of the Kayu Laut Community Health Center (UPTD) in South Panyabungan, indications of fluctuating attendance and suboptimal work outcomes highlight the importance of examining these variables. A quantitative associative approach was applied using total sampling of 84 employees, with data collected through a Likert-scale questionnaire measuring work discipline, motivation, and performance. The data were analyzed using multiple linear regression supported by t-tests, F-tests, and coefficient of determination (R²). The findings indicate that work discipline has a positive and significant effect on employee performance, as does work motivation. Simultaneously, both variables contribute significantly to performance improvement, explaining 63.2% of the variance, while the remaining proportion is influenced by other factors beyond the model. These results confirm that discipline and motivation function as complementary determinants in enhancing employee effectiveness within healthcare services. The study contributes to the limited empirical evidence on human resource performance in primary healthcare settings and underscores the importance of organizational strategies that strengthen discipline and foster motivation to achieve optimal service quality.